Pegylated Interferon Alpha-2b in Patients With Polycythemia Vera and Essential Thrombocythemia in the Real World - Sun, Yingxin; Cai, Yifeng; Cen, Jiannong; Zhu, Mingqing; Pan, Jinlan; Wang, Qian; Wu, Depei; Chen, Suning (Frontiers in Oncology, 2021)
Several clinical trials have shown promising efficacy of pegylated interferon (Peg-IFN) in the first- and second-line polycythemia vera (PV) and essential thrombocythemia (ET). However, the efficacy and safety of Peg-IFN in the real world have rarely been reported. Hence, we conducted a prospective, single-center, single-arm, open exploratory study, which aimed to explore the hematologic response, molecular response, safety, and tolerability of patients with PV and ET treated with Peg-IFN in the real world. This study included newly diagnosed or previously treated patients with PV and ET, aged 18 years or older, admitted to the Department of Hematology of the First Affiliated Hospital of Soochow University from November 2017 to October 2019. The results revealed that complete hematological response (CHR) was achieved in 66.7% of patients with PV and 76.2% of patients with ET, and the molecular response was obtained in 38.5% of patients with PV and 50% of patients with ET after 48 weeks of Peg-IFN treatment. Peg-IFN is safe, effective and well tolerated in most patients. In the entire cohort, 4 patients (9.1%) discontinued treatment due to drug-related toxicity. In conclusion, Peg-IFN is a promising strategy in myeloproliferative neoplasms (MPNs), and Peg-IFN alone or in combination with other drugs should be further explored to reduce treatment-related toxicity and improve tolerability.